Understanding Union Commitment Among Young Workers: A Cross-Theoretical Perspective - Hennebert, Marc-Antonin; Fortin-Bergeron, Chloe; Doucet, Olivier (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2021)
This study aims to shed light on the main determinants of and barriers to union commitment among young workers and, more generally, the relationship young workers have with union life. So far, the relationship between young workers and unionism has been examined mainly in terms of the challenges of access to unionization that confront young workers, a group generally underrepresented in union membership. The more specific issue of union commitment among young workers, once they become unionized, has remained largely underexplored in the literature. Using quantitative and qualitative data from an empirical survey of young unionized workers in the Quebec public service, our study identifies and compares the main factors that explain union commitment among young unionized workers and the theoretical underpinnings. It also seeks to shed light on the barriers to this commitment and identifies the organizational measures that could facilitate union commitment among young workers, based on the perceptions expressed by young union members. Our findings indicate that unions should adopt multidimensional organizational measures to foster union commitment among young workers, with a first step being to increase personalized contact between local union representatives and young members. Such investments at the local level are critical, as shown by our quantitative and qualitative findings. Thus, any reform or measure aimed at encouraging union involvement of young workers should not be limited merely to structural aspects but should also take into account the attitudinal and relational underpinnings of young workers’ commitment to their union. By shifting the focus from youth unionization to young members’ involvement in union bodies, our study will contribute to debate about union representation and the generational renewal of the labour movement’s activist base.